Identifying the major intermediate species by combining time-resolved X-ray solution scattering and X-ray absorption spectroscopy. Issue 36 (24th August 2015) - Kim, Kyung Hwan; Kim, Jeongho; Oang, Key Young; Lee, Jae Hyuk; Grolimund, Daniel; Milne, Christopher J.; Penfold, Thomas J.; Johnson, Steven L.; Galler, Andreas; Kim, Tae Wu; Kim, Jong Goo; Suh, Deokbeom; et al.
Abstract : We identify a major transient species formed in the photolysis of CHI3 by combining time-resolved X-ray liquidography (TRXL) and time-resolved X-ray absorption spectroscopy (TR-XAS). Abstract : Identifying the intermediate species along a reaction pathway is a first step towards a complete understanding of the reaction mechanism, but often this task is not trivial. There has been a strong on-going debate: which of the three intermediates, the CHI2 radical, the CHI2 –I isomer, and the CHI2 + ion, is the dominant intermediate species formed in the photolysis of iodoform (CHI3 )? Herein, by combining time-resolved X-ray liquidography (TRXL) and time-resolved X-ray absorption spectroscopy (TR-XAS), we present strong evidence that the CHI2 radical is dominantly formed from the photolysis of CHI3 in methanol at 267 nm within the available time resolution of the techniques (∼20 ps for TRXL and ∼100 ps for TR-XAS). The TRXL measurement, conducted using the time-slicing scheme, detected no CHI2 –I isomer within our signal-to-noise ratio, indicating that, if formed, the CHI2 –I isomer must be a minor intermediate. The TR-XAS transient spectra measured at the iodine L1 and L3 edges support the same conclusion. The present work demonstrates that the application of these two complementary time-resolved X-ray methods to the same system can provide a detailed understanding of the reaction mechanism.